FINANCIAL PERFORMANCE, MACRO ECONOMICS, AND FIRM VALUE WITH CAPITAL STRUCTURE AS MODERATING VARIABLE - Partogian Sormin; Mulyadi Noto Soetardjo; Tasya Salfira (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
The objective of this study is to figure out what firm worth is meant for by monetary execution and macroeconomic elements. Companies in the non-cyclical consumer goods industry that were listed on the Indonesia Stock Exchange between 2016 and 2020 were the focus of this study. Multiple regression analysis and purposeful sampling were utilized for the data analysis. Macroeconomics and monetary execution are the free factors in this examination. Financial performance is assessed using indicators like leverage, dividend payments, and profit margin. Macroeconomic metrics include inflation, interest rates, and the gross domestic product. The study's findings demonstrate that firm value is affected simultaneously by macroeconomics and financial performance. After that, leverage can make a company's value more proportional to its gross profit margin and dividend payments. Firm value is unaffected by gross domestic product, interest rates, or inflation, despite the fact that financial performance has a positive impact. This study used leverage as a moderating variable, and the results were able to strengthen the connection between firm value and dividend payout. The novelty or distinction between this study and previous ones is as follows: Leverage was typically used as an independent variable by previous researchers. Partners will find this encouraging news.